2022
DOI: 10.2217/imt-2021-0338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neoadjuvant Therapy on Tumor Tissue PD-L1 and VISTA Expression Levels in Non-Small-Cell Lung Cancer

Abstract: Background: PD-L1 and VISTA are important checkpoint control stations and play an immunomodulatory role in patients with non-small-cell lung cancer. Method: The expression levels of PD-L1 and VISTA between pre- and post-treatment tumor tissue were compared. Results: While PD-L1 expression was >1% in 35% of patients before neoadjuvant therapy, PD-L1 expression was >1% in 65% of patients after treatment (p = 0.004). VISTA expression was >1% in 41% of patients before treatment, and this rate was 65% afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For patients with a CPS between 1 and 10, radiotherapy could be added to the treatment plan to improve the immune microenvironment, promote tumor antigen release, and upregulate PD-L1 expression. 55 Our study revealed that the drug acquisition cost of serplulimab accounts for 91.91% of the total incremental cost, indicating that the cost of obtaining serplulimab is significantly higher than that of chemotherapy drugs. Lowering the price of serplulimab could significantly enhance its cost-effectiveness, a finding supported by our model's one-way deterministic sensitivity analysis results.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For patients with a CPS between 1 and 10, radiotherapy could be added to the treatment plan to improve the immune microenvironment, promote tumor antigen release, and upregulate PD-L1 expression. 55 Our study revealed that the drug acquisition cost of serplulimab accounts for 91.91% of the total incremental cost, indicating that the cost of obtaining serplulimab is significantly higher than that of chemotherapy drugs. Lowering the price of serplulimab could significantly enhance its cost-effectiveness, a finding supported by our model's one-way deterministic sensitivity analysis results.…”
Section: Discussionmentioning
confidence: 74%
“…For patients with a CPS between 1 and 10, radiotherapy could be added to the treatment plan to improve the immune microenvironment, promote tumor antigen release, and upregulate PD-L1 expression. 55…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy upregulates the expression of PD‐1 in NK cells and PD‐L1 in NPC cells, blocks the anti‐tumor function of NK cells, and reduces NPC cells recognition, resulting in tumor cells evading immune surveillance (Makowska et al, 2021). Neoadjuvant therapy, including chemotherapy and radiotherapy, was found to increase the expression of PD‐L1 and VISTA in non‐small‐cell lung cancer (Akdoğan et al, 2022). Whole‐body irradiation in mice resulted in significantly elevated PD‐1 expression in both CD4+ and CD8+ T cell populations and persisted until the 4th week, affecting T cell activation (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations have shown that higher VISTA expression is related to better clinical results, whereas PD-L1 expression is associated with worse outcomes in patients with malignant cell carcinoma [17]. VISTA is mostly expressed on TME immune cells in most human malignancies and mouse models, while it has also been found in lung, kidney, and colorectal tumor cells, endometrial tissue, and human ovaries [19,20,43,47,[51][52][53][54][55][56][57][58]. Tumor immunity is impacted by VISTA in both positive and negative ways.…”
Section: Introductionmentioning
confidence: 99%